Political autobiographies and memoirs in antiquity a Brill companion - Marasco, Gabriele 1950- (Leiden [u.a.] Brill, 2011)
Abbreviations -- Classical Greece/ V.J. Gray -- Royal autobiography in the Hellenistic age/ Cinzia Bearzot -- The Hellenistic age: autobiography and political struggles/ Gabriele Marasco -- Republican Rome: autobiography and political struggles/ J.M. Candau -- The late republic: autobiographies and memoirs in the age of the civil wars/ Jeffrey Tatum -- Caesar and the Corpus Caesarianum/ Marc Mayer -- The Augustan Age/ Joseph Geiger -- Augustus: the emperor writes his own account/ Ronald Thomas Ridley -- The early empire/ Pere Villalba Varneda -- The second and third century/ Richard Westall and Frederick Brenk -- The late empire/ Hartmut Leppin
Abbreviations -- Classical Greece/ V.J. Gray -- Royal autobiography in the Hellenistic age/ Cinzia Bearzot -- The Hellenistic age: autobiography and political struggles/ Gabriele Marasco -- Republican Rome: autobiography and political struggles/ J.M. Candau -- The late republic: autobiographies and memoirs in the age of the civil wars/ Jeffrey Tatum -- Caesar and the Corpus Caesarianum/ Marc Mayer -- The Augustan Age/ Joseph Geiger -- Augustus: the emperor writes his own account/ Ronald Thomas Ridley -- The early empire/ Pere Villalba Varneda -- The second and third century/ Richard Westall and Frederick Brenk -- The late empire/ Hartmut Leppin.
Literaturangaben
Mit Reg
Archivierung prüfen
Keywords: Classical biography -- History and criticism; Biography as a literary form; Autobiography; Aufsatzsammlung